Co-doped silicon-based materials, methods of making and using the same
Patent Information
- Application Number
- CN202311852644.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-28
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2043-12-28
AI Technical Summary
中国专利(如CN116799187A)将锂氮化合物与包碳后的氧化亚硅进行物理混合,得到氮掺杂的预锂化氧化亚硅材料,这种方法可以在不牺牲循环稳定性的前提下提高氧化亚硅负极材料的首次库伦效率,但是物理混合的方式容易导致锂源与氧化亚硅材料混合不均匀
[0038]在一些实施方案中,负极活性材料应用在锂离子电池中,将该硅基负极材料在锂离子电池中进行应用,可提高电池的容量和能量密度。
Smart Images

Figure CN117810419B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of materials preparation technology, and in particular to co-doped silicon-based materials, their preparation methods, and applications. Background Technology
[0002] With the continuous development of portable electronic products, electric vehicles, and energy storage devices, existing commercially available lithium-ion batteries made with graphite anodes are no longer sufficient to meet market demands for high energy density, long lifespan, and safety. Therefore, developing next-generation lithium-ion battery anode materials is urgently needed. Among numerous alternative anode materials, silicon is considered one of the most promising due to its theoretical specific capacity of up to 4200 mAh / g. However, silicon anode materials suffer from low charge-discharge efficiency during the first cycle of lithium-ion batteries. Furthermore, during continuous charge-discharge processes, lithium insertion / extraction in silicon anode materials leads to volume expansion, resulting in repeated rupture and formation of the SEI film, consuming large amounts of electrolyte and active lithium ions.
[0003] To address these issues, pre-lithiation technology has been employed to replenish the lithium source for the anode material, offsetting the irreversible lithium consumption caused by the formation of the SEI film in lithium-ion batteries. This improves the initial coulombic efficiency, increasing the battery's capacity and energy density. Chinese patents (such as CN116799187A) physically mix lithium-nitrogen compounds with carbon-coated silicon suboxide to obtain nitrogen-doped pre-lithiated silicon suboxide material. This method can improve the initial coulombic efficiency of the silicon suboxide anode material without sacrificing cycle stability; however, physical mixing can easily lead to uneven mixing of the lithium source and silicon suboxide material. Another example is Chinese patent (CN112551522A), which uses lithium hydroxide and fluorinated organic acids to react and obtain lithium salts, achieving pre-lithiation of silicon suboxide material. However, the use of fluorides can easily cause harm to human health and the environment.
[0004] Therefore, developing a high-capacity, high-efficiency silicon-based anode material is of great significance for promoting the commercial application of silicon-based anode materials in lithium-ion batteries. Summary of the Invention
[0005] Based on the above problems, the purpose of this invention is to provide a co-doped silicon-based material, its preparation method and application. Using the co-doped silicon-based material of this invention as a silicon-based anode material can significantly improve the first coulombic efficiency of the silicon-based anode material, improve the conductivity of the silicon-based anode material, and increase the capacity and energy density of the battery.
[0006] To achieve the above objectives, the first aspect of the present invention provides a co-doped silicon-based material, comprising silicon particles and a first carbon coating layer covering the surface of the silicon particles, forming silicon particles containing the first carbon coating layer, wherein a plurality of silicon particles containing the first carbon coating layer are embedded in a second carbon coating layer, the first carbon coating layer being bonded to the silicon particles by chemical bonds, and the first carbon coating layer containing nitrogen and lithium elements.
[0007] In the co-doped silicon-based material of the present invention, a first carbon coating layer is formed on the surface of silicon particles. The carbon layer in the first carbon coating layer is tightly bonded to the silicon particles by chemical bonds, and N and Li elements are uniformly distributed on the first carbon coating layer. N doping can improve the conductivity of the silicon-based material. As a silicon-based anode material, pre-lithiation can significantly improve the first coulombic efficiency of the silicon-based anode material, improve the capacity and energy density of the battery. Moreover, the chemical bond between the first carbon coating layer and the silicon particles can improve the cycle stability of the anode material compared with conventional physical coating.
[0008] In some implementations, the coating integrity of the co-doped silicon-based material is I, and satisfies 0 ≤ I < 0.5.
[0009] The formula for calculating the coating integrity I is I = (V1 - V0) / V0. The test method for coating integrity I is as follows: 50g of the co-doped silicon-based material, 50g of water and 5g of dispersant are mixed evenly in a container. The mixed slurry is then filled into a syringe and sealed. The volume V0 occupied by the slurry is recorded. The sealed syringe is placed in a 60°C oven for 48 hours. Then the syringe is removed and the syringe reading is recorded as V1. The gas produced by the reaction of nano-silicon with water is V1 - V0.
[0010] In some embodiments, the mass percentage of nitrogen in the co-doped silicon-based material is 8-15%.
[0011] In some embodiments, the mass percentage of lithium in the co-doped silicon-based material is 6-12%.
[0012] In some implementations, the particle size D50 of the co-doped silicon-based material is 3 to 50 μm.
[0013] In some embodiments, the silicon particles are at least one of nano-silicon or silicon suboxide.
[0014] In some implementations, the silicon particles are nano-silicon with a particle size D50 of 1 to 150 nm.
[0015] In some implementations, the silicon particles are nano-silicon, with a grain size of 1 to 15 nm.
[0016] In some implementations, the silicon particles are silicon suboxide, and the silicon suboxide is SiO xx in the equation satisfies 0 < x ≤ 0.8.
[0017] In some implementations, the thickness of the first carbon coating layer is 0.3 to 1.0 μm.
[0018] In some implementations, the molar ratio of Li content to silicon particle content in the first carbon coating layer is 0.05 to 0.25:1.
[0019] In some implementations, the molar ratio of nitrogen content to silicon particle content in the first carbon coating layer is 0.05 to 0.25:1.
[0020] In some implementations, the second carbon coating layer is a single carbon coating layer or at least two carbon coating layers.
[0021] In some implementations, the second carbon coating layer is a single-layer carbon coating layer with a thickness of 0.5 to 2 μm.
[0022] A second aspect of the present invention provides a method for preparing co-doped silicon-based materials, comprising the steps of:
[0023] S1 dissolves the double-bonded ammonium chloride salt compound in the first solvent, adds silicon particles and stirs until homogeneous to obtain solution A;
[0024] S2 dissolves the lithium-nitrogen compound in a second solvent to obtain solution B;
[0025] S3 adds solution B dropwise to solution A while stirring. After the addition is complete, the mixture is reacted at a certain temperature. After the reaction is complete, the mixture is centrifuged and freeze-dried to obtain powder precursor A.
[0026] S4 carbonizes and sinters the powder precursor A to obtain precursor B;
[0027] S5 carbon-coated precursor B to obtain co-doped silicon-based material.
[0028] In the preparation method of co-doped silicon-based material of the present invention, the principle of Michael addition reaction is utilized to attach lithium nitrogen compound to the surface of silicon particles in the form of chemical bonds. Compared with the conventional method of physical blending pre-lithiation, the preparation method provided by the present invention can make lithium more uniformly dispersed in silicon-based material, and at the same time, nitrogen element is introduced, which can improve the conductivity of silicon-based material to a certain extent.
[0029] In some embodiments, the double-bonded ammonium chloride salt compound is selected from at least one of dimethyl diallyl ammonium chloride, diethyl diallyl ammonium chloride, triallyl methyl ammonium chloride, and allyl trimethyl ammonium chloride.
[0030] In some embodiments, the first solvent is selected from at least one of water, ethanol, isopropanol, n-butanol, and diethyl ether.
[0031] In some implementations, the molar ratio of the double-bonded ammonium chloride salt to the silicon particles is 1:4 to 1:40.
[0032] In some embodiments, the lithium nitrogen compound is selected from at least one of lithium amino, lithium dimethylamine, lithium diethylamino, and lithium diisopropylamino.
[0033] In some embodiments, the molar ratio of the amino content of the lithium nitrogen compound to the double bond content of the double-bonded ammonium chloride salt is 1 to 5:1.
[0034] In some embodiments, the second solvent is selected from at least one of water, ethanol, isopropanol, n-butanol, and diethyl ether.
[0035] In some implementations, the carbonization temperature is between 500 and 1200°C.
[0036] In some implementations, in step S3, the reaction temperature is controlled at 0-5°C and the reaction time is 48-96 h.
[0037] The third aspect of this invention provides the application of silicon-based materials in negative electrode active materials. As silicon-based negative electrode materials, these materials exhibit excellent conductivity, initial coulombic efficiency, and cycle stability, thereby improving the battery capacity and energy density.
[0038] In some implementations, the negative electrode active material is used in lithium-ion batteries. Applying this silicon-based negative electrode material to lithium-ion batteries can improve the battery's capacity and energy density. Attached Figure Description
[0039] Figure 1 This is a schematic diagram of the structure of the co-doped silicon-based material of the present invention.
[0040] Figure 2 This is a SEM image of the co-doped silicon-based material from Example 1. Detailed Implementation
[0041] The co-doped silicon-based material of this invention can be used alone as a negative electrode active material, or it can be used in combination with other negative electrode active materials (such as natural graphite, artificial graphite, soft carbon and / or hard carbon). The co-doped silicon-based material can be applied as a negative electrode active material in lithium-ion batteries, significantly improving the capacity, initial coulombic efficiency, conductivity, and energy density of lithium-ion batteries.
[0042] Please refer to Figure 1 The co-doped silicon-based material includes silicon particles and a first carbon coating layer covering the surface of the silicon particles, forming silicon particles containing the first carbon coating layer. Several silicon particles containing the first carbon coating layer are embedded in a second carbon coating layer. The first carbon coating layer is chemically bonded to the silicon particles, and the first carbon coating layer contains nitrogen and lithium elements.
[0043] The coating integrity of the co-doped silicon-based material is I, satisfying 0 ≤ I < 0.5. For example, I can be, but is not limited to, 0.10, 0.15, 0.20, 0.25, 0.30, 0.35, 0.40, or 0.45. When the carbon coating integrity is within this range, the carbon coating layer provides better coverage of the silicon particles, preventing direct contact between the silicon particles and the electrolyte, thus avoiding the formation of an unstable SEI film. Simultaneously, the first carbon coating layer bonds to the silicon particles via chemical bonds, resulting in stronger bonding compared to traditional physical coating, which is more conducive to forming a stable structure. Furthermore, the first carbon coating layer contains uniformly distributed N and Li elements. N elements improve the conductivity of the co-doped silicon-based material, while Li elements form a uniformly thick SEI film, reducing Li loss in the electrolyte, thereby improving the first-efficiency and cycle performance of the co-doped silicon-based material.
[0044] The formula for calculating the coating integrity I is I = (V1 - V0) / V0. The test method for coating integrity I is as follows: 50g of the co-doped silicon-based material, 50g of water and 5g of dispersant are mixed evenly in a container. The mixed slurry is then filled into a syringe and sealed. The volume V0 occupied by the slurry is recorded. The sealed syringe is placed in a 60°C oven for 48 hours. Then the syringe is removed and the syringe reading is recorded as V1. The gas produced by the reaction of nano-silicon with water is V1 - V0.
[0045] The mass percentage of nitrogen in the co-doped silicon-based material is 8% to 15%. As an example, the mass percentage of nitrogen in the co-doped silicon-based material can be, but is not limited to, 8%, 9%, 10%, 11%, 12%, 13%, 14%, and 15%. Setting the mass percentage of nitrogen in the co-doped silicon-based material within a certain range, and providing a compound including double-bonded ammonium chloride and lithium-nitrogen compounds, ensures that sufficient double-bonded ammonium chloride compounds are adsorbed on the surface of the silicon particles, guaranteeing the integrity of the first carbon coating layer; furthermore, it also ensures that sufficient lithium-nitrogen compounds react with the double-bonded ammonium chloride compounds, ensuring that Li elements are uniformly distributed on the first carbon coating layer.
[0046] The mass percentage of lithium in co-doped silicon-based materials is 6%–12%. For example, the mass percentage of lithium in co-doped silicon-based materials can be, but is not limited to, 6%, 7%, 8%, 9%, 10%, 11%, and 12%. Setting the mass percentage of lithium in co-doped silicon-based materials within a certain range ensures sufficient lithium to form the SEI film, avoiding lithium consumption in the electrolyte. When the mass percentage of lithium in the co-doped silicon-based materials is less than 6%, insufficient Li is provided; when it is greater than 12%, Li is wasted.
[0047] The particle size D50 of the co-doped silicon-based material is 3 to 50 μm, optionally about 3 to 50 μm, 5 to 50 μm, 10 to 50 μm, 20 to 50 μm, 5 to 40 μm, 10 to 30 μm, 3 to 40 μm, preferably, but not limited to 3 μm, 5 μm, 7 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm.
[0048] The silicon particles are at least one of nano-silicon or silicon suboxide. In one embodiment, the silicon particles are nano-silicon. Preferably, the particle size D50 of the nano-silicon is 1 to 150 nm. Optionally, it is about 1 to 140 nm, about 5 to 150 nm, about 10 to 150 nm, about 20 to 150 nm, about 40 to 150 nm, about 60 to 150 nm, about 20 to 120 nm, about 40 to 120 nm, or about 20 to 100 nm. Preferably, it can be, but is not limited to, 1 nm, 5 nm, 10 nm, 20 nm, 40 nm, 80 nm, 120 nm, 130 nm, 140 nm, or 150 nm. Further, the grain size of the nano-silicon is 1 to 15 nm, optionally about 1 to 12 nm, about 1 to 10 nm, about 1 to 8 nm, about 2 to 15 nm, about 2 to 12 nm, about 2 to 8 nm, about 3 to 15 nm, about 3 to 12 nm, preferably, but not limited to, 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, 11 nm, 12 nm, 13 nm, 14 nm, and 15 nm. In another embodiment, the silicon particles are silicon suboxide, preferably, silicon suboxide SiO x In this context, x is greater than 0 and less than or equal to 0.8, and x can be, but is not limited to, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, or 0.8. In other embodiments, the silicon particles are a mixture of nano-silicon and silicon suboxide.
[0049] Utilizing the principle of Michael addition reaction, lithium-nitrogen compounds are chemically bonded to the surface of silicon particles to form a first carbon coating layer. This method allows for more uniform dispersion of lithium in silicon-based materials and also introduces nitrogen, which can improve the conductivity of silicon-based materials to a limited extent. Preferably, the thickness of the first carbon coating layer is 0.3 μm to 1.0 μm, optionally about 0.3 μm to 0.5 μm, 0.5 μm to 0.8 μm, or 0.8 μm to 1.0 μm, and more preferably, but not limited to, 0.3 μm, 0.35 μm, 0.4 μm, 0.45 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, or 1.0 μm.
[0050] The molar ratio of Li content to silicon particle content in the first carbon coating layer is 0.05 to 0.25:1, optionally about 0.05 to 0.20:1, 0.05 to 0.15:1, 0.1 to 0.25:1, 0.1 to 0.2:1, and specifically, but not limited to 0.05:1, 0.1:1, 0.15:1, 0.2:1, and 0.25:1.
[0051] The molar ratio of N content to silicon particle content in the first carbon coating layer is 0.05 to 0.25:1, optionally about 0.05 to 0.20:1, 0.05 to 0.15:1, 0.1 to 0.25:1, 0.1 to 0.2:1, specifically, but not limited to 0.05:1, 0.1:1, 0.15:1, 0.2:1, 0.25:1.
[0052] The method for preparing the co-doped silicon-based material of the present invention includes the following steps:
[0053] S1 dissolves the double-bonded ammonium chloride salt compound in the first solvent, adds silicon particles and stirs until homogeneous to obtain solution A;
[0054] S2 dissolves the lithium-nitrogen compound in a second solvent to obtain solution B;
[0055] S3 adds solution B dropwise to solution A while stirring. After the addition is complete, the mixture is reacted at a certain temperature. After the reaction is complete, the mixture is centrifuged and freeze-dried to obtain powder precursor A.
[0056] S4 carbonizes and sinters the powder precursor A to obtain precursor B;
[0057] S5 carbon-coated precursor B to obtain co-doped silicon-based material.
[0058] The double-bonded ammonium chloride salt compound of the present invention is selected from at least one of dimethyl diallyl ammonium chloride, diethyl diallyl ammonium chloride, triallyl methyl ammonium chloride, and allyl trimethyl ammonium chloride. For example, the double-bonded ammonium chloride salt compound is dimethyl diallyl ammonium chloride, or a mixture of dimethyl diallyl ammonium chloride and diethyl diallyl ammonium chloride, but is not limited thereto.
[0059] The first solvent of the present invention is selected from at least one of water, ethanol, isopropanol, n-butanol, and diethyl ether. As an example, the first solvent is water, preferably cold water, which can be selected according to the dissolution of double-bonded ammonium chloride salt compounds. For example, the first solvent is ethanol, but it is not limited thereto.
[0060] The molar ratio of the double-bonded ammonium chloride salt to silicon particles in this invention is 1:4 to 1:40, preferably about 1:6 to 1:40, 1:10 to 1:40, 1:20 to 1:40, 1:4 to 1:30, 1:5 to 1:30, 1:4 to 1:35. More specifically, the molar ratio of the double-bonded ammonium chloride salt to silicon particles may be, but is not limited to, 1:4, 1:8, 1:12, 1:16, 1:20, 1:25, 1:30, 1:35, or 1:40.
[0061] The lithium nitrogen compound of the present invention is selected from at least one of lithium amino, lithium dimethylamine, lithium diethylamino, and lithium diisopropylamino. As an example, the lithium nitrogen compound is lithium amino or lithium diethylamino, or it may be a mixture of lithium dimethylamino and lithium diisopropylamino.
[0062] The molar ratio of the amino content to the double bond content of the double-bonded ammonium chloride salt in the lithium nitrogen compound of the present invention is 1 to 5:1, about 1 to 3:1, about 1 to 2:1, and, by way of example, about 1:1 or 2:1.
[0063] The second solvent of the present invention is selected from at least one of water, ethanol, isopropanol, n-butanol, and diethyl ether. As an example, the second solvent is water, preferably cold water, which can be selected according to the dissolution of double-bonded ammonium chloride salt compounds. For example, the second solvent is ethanol, but it is not limited thereto.
[0064] The carbonization temperature of this invention is 500 to 1200°C, approximately 500 to 1000°C, approximately 600 to 1200°C, approximately 600 to 1000°C, approximately 700 to 1200°C, specifically, but not limited to 500°C, 600°C, 700°C, 800°C, 900°C, 1000°C, 1100°C, and 1200°C. The carbonization sintering time is 2 hours to 8 hours, specifically, but not limited to 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, and 8 hours. The heating rate for carbonization sintering is from 0.1℃ / min to 10.0℃ / min, and may be, but is not limited to, 0.1℃ / min, 0.5℃ / min, 1.0℃ / min, 2.0℃ / min, 3.0℃ / min, 4.0℃ / min, 5.0℃ / min, 6.0℃ / min, 7.0℃ / min, 8.0℃ / min, 9.0℃ / min, and 10.0℃ / min. After carbonization and sintering, the material is cooled to room temperature and then broken up. The speed used for breaking up is 500 r / min to 3000 r / min. For example, the speed can be, but is not limited to, 500 r / min, 600 r / min, 700 r / min, 800 r / min, 900 r / min, 1000 r / min, 1100 r / min, 1200 r / min, 1300 r / min, 1400 r / min, 1500 r / min, 2000 r / min, 2500 r / min, and 3000 r / min. The breaking up time is 30 min to 120 min. For example, the breaking up time can be, but is not limited to, 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, 100 min, 110 min, and 120 min.
[0065] In step S3 of this invention, the reaction temperature is controlled at 0 to 5°C, employing a low-temperature reaction to ensure the reaction proceeds. The reaction time is 48-96 hours, for example, 72 hours, but is not limited to this.
[0066] The carbon coating in step S5 of this invention can be gas-phase carbon coating (CVD carbon coating), solid-phase carbon coating, or liquid-phase carbon coating. Of course, other coating methods such as plasma coating can also be used, as long as the coating can form an outer carbon layer. The formed outer carbon layer can be one, two, three, etc. As an example, the carbon coating formed in step S5 is a single-layer carbon coating layer. Preferably, the thickness of the single-layer carbon coating layer is 0.5 μm to 2 μm, optionally about 0.5 to 1.5 μm, 0.5 to 1 μm, 1 to 2 μm, specifically about 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, but not limited thereto. The silicon-carbon composite material of this invention is not limited to the carbon coating method, nor is it limited to the number of carbon coating layers.
[0067] The gas-phase carbon coating is performed using chemical vapor deposition (CVD), and may include the steps of: adding precursor B to a CVD furnace, and then introducing a gas-phase carbon source under a protective atmosphere to react and obtain a co-doped silicon-based material. In this gas-phase carbon coating, the protective atmosphere may be, but is not limited to, at least one of argon, nitrogen, and helium. The flow rate of the protective atmosphere is 4 L / min to 10 L / min; for example, the flow rate may be, but is not limited to, 4 L / min, 5 L / min, 6 L / min, 7 L / min, 8 L / min, 9 L / min, or 10 L / min. The reaction temperature is 700°C to 1100°C; for example, the reaction temperature may be, but is not limited to, 700°C, 800°C, 900°C, 1000°C, or 1100°C. The heating rate is from 5°C / min to 10°C / min. For example, the heating rate may be, but is not limited to, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, or 10°C / min. The gaseous carbon source includes methane, ethane, propane, ethylene, propylene, acetylene, or propyne. The gas flow rate of the gaseous carbon source is from 0.5 L / min to 3.0 L / min. For example, the gas flow rate may be, but is not limited to, 0.5 L / min, 1.0 L / min, 1.5 L / min, 2.0 L / min, 2.5 L / min, or 3.0 L / min. The time for introducing the gaseous carbon source is from 4 h to 8 h. For example, the time for introducing the gaseous carbon source may be, but is not limited to, 4 h, 5 h, 6 h, 7 h, or 8 h.
[0068] Liquid-phase carbon coating may include the following steps: uniformly mixing an organic carbon source, a solvent, and precursor B to obtain a mixed solution; spray-drying the mixed solution and then carbonizing it to obtain a co-doped silicon-based material. In this liquid-phase carbon coating, the organic carbon source may be, but is not limited to, at least one of polyvinyl alcohol, glucose, and sucrose. The solvent may be, but is not limited to, at least one of water, ethanol, acetone, and isopropanol. The organic carbon source dissolves in the solvent at a temperature ranging from 25°C to 70°C. For example, the dissolution temperature may be, but is not limited to, 25°C, 27°C, 30°C, 33°C, 35°C, 37°C, 40°C, 43°C, 46°C, 48°C, 50°C, 52°C, 55°C, 58°C, 60°C, 62°C, 65°C, 68°C, and 70°C. The reaction can be accelerated by stirring during dissolution, and the stirring time can be from 0.5 h to 2.0 h. For example, the stirring time can be, but is not limited to, 0.5 h, 0.7 h, 0.9 h, 1.1 h, 1.3 h, 1.5 h, 1.7 h, 1.9 h, and 2.0 h. Carbonization is carried out under a protective atmosphere, including at least one of nitrogen, argon, and helium. The carbonization temperature is from 700 °C to 1100 °C. For example, the carbonization temperature can be, but is not limited to, 700 °C, 800 °C, 900 °C, 1000 °C, and 1100 °C. The carbonization time is from 2 h to 6 h. For example, the carbonization time can be, but is not limited to, 2 h, 3 h, 4 h, 5 h, and 6 h. The heating rate of carbonization is from 1 °C / min to 5 °C / min. For example, the heating rate can be, but is not limited to, 1 °C / min, 2 °C / min, 3 °C / min, 4 °C / min, and 5 °C / min.
[0069] Solid-phase carbon coating may include the steps of: mixing and dispersing a solid-phase carbon source and precursor B, and then carbonizing under a protective atmosphere to obtain a co-doped silicon-based material. In this solid-phase coating, the solid-phase carbon source may be, but is not limited to, solid pitch, glucose, sucrose, or phenolic resin. Mixing and dispersion can be performed using general-purpose equipment, and the parameters used for mixing can be conventional. The carbonization temperature is between 700°C and 1100°C; for example, the carbonization temperature may be, but is not limited to, 700°C, 800°C, 900°C, 1000°C, or 1100°C. The carbonization time is between 2 hours and 6 hours; for example, the carbonization time may be, but is not limited to, 2 hours, 3 hours, 4 hours, 5 hours, or 6 hours. The carbonization heating rate is between 1°C / min and 5°C / min; for example, the heating rate may be, but is not limited to, 1°C / min, 2°C / min, 3°C / min, 4°C / min, or 5°C / min.
[0070] After carbon coating, the material can be cooled, dispersed, and sieved sequentially. Cooling can be done naturally to room temperature or accelerated by external force. Dispersion can be, but is not limited to, dispersing VC. The dispersion speed is between 500 r / min and 3000 r / min. For example, the dispersion speed can be, but is not limited to, 500 r / min, 600 r / min, 700 r / min, 800 r / min, 900 r / min, 1000 r / min, 1100 r / min, 1200 r / min, 1300 r / min, 1400 r / min, 1500 r / min, 2000 r / min, 2500 r / min, and 3000 r / min. The dispersing time is 30 to 120 minutes. For example, the dispersing time can be, but is not limited to, 30, 40, 50, 60, 70, 80, 90, 100, 110, and 120 minutes. The sieve used for screening is 100 to 500 mesh. For example, the sieve can be, but is not limited to, 100, 130, 150, 170, 200, 230, 250, 300, 350, 400, 450, and 500 mesh.
[0071] To better illustrate the purpose, technical solution, and beneficial effects of this invention, the invention will be further described below with reference to specific embodiments. It should be noted that the following embodiments are further explanations of this invention and should not be construed as limiting it.
[0072] Example 1
[0073] This embodiment describes a method for preparing a co-doped silicon-based material, which includes the following steps.
[0074] S1 Weigh a certain amount of dimethyl diallyl ammonium chloride and dissolve it in cold water. After the dissolution is complete, add a certain proportion of nano-silicon powder and stir evenly to obtain solution A. The molar ratio of dimethyl diallyl ammonium chloride to nano-silicon is 1:10.
[0075] S2 Weigh a certain amount of lithium amino acid and dissolve it in cold water, stir it evenly to obtain solution B; wherein, the molar ratio of lithium amino acid to dimethyl diallyl ammonium chloride in step S1 is 2:1.
[0076] S3. Solution B from step S2 is slowly added dropwise to solution A from step S1. Solution A is stirred throughout the addition process, and the temperature of the solution system is kept between 0-5℃. After the addition of solution B is complete, the reaction is carried out at a low temperature of 5℃ for 72 hours, and then centrifuged and freeze-dried to obtain precursor A.
[0077] S4 Precursor A was carbonized and sintered in a nitrogen atmosphere at a temperature of 700℃, a heating rate of 1℃ / min, and a sintering time of 4h. After sintering, it was naturally cooled to room temperature and then dispersed at 1000r / min for 60min to obtain precursor B.
[0078] S5 involves CVD carbon coating of precursor B, heating it to 800℃ at 5℃ / min, and then introducing nitrogen and acetylene at a gas flow rate of 1.5L / min for 3 hours. After naturally cooling to room temperature, the mixture is dispersed and sieved to obtain the co-doped silicon-based material.
[0079] The co-doped silicon-based material prepared in Example 1 was subjected to SEM testing, and the results are as follows: Figure 2 As shown, by Figure 2 It can be seen that its particle size D50 is 8.3μm. Further analysis and testing revealed that the silicon particles are coated with a first carbon coating layer containing N and Li elements. The thickness of the first carbon coating layer is about 0.35μm, and the thickness of the second carbon coating layer is about 0.8μm.
[0080] Example 2
[0081] This embodiment describes a method for preparing a co-doped silicon-based material, which includes the following steps.
[0082] S1 Weigh a certain amount of dimethyl diallyl ammonium chloride and dissolve it in cold water. After the dissolution is complete, add a certain proportion of nano-silicon powder and stir evenly to obtain solution A. The molar ratio of dimethyl diallyl ammonium chloride to nano-silicon is 1:20.
[0083] S2 Weigh a certain amount of lithium amino acid and dissolve it in cold water, stir it evenly to obtain solution B; wherein, the molar ratio of lithium amino acid to dimethyl diallyl ammonium chloride in step S1 is 2:1.
[0084] S3. Solution B from step S2 is slowly added dropwise to solution A from step S1. Solution A is stirred throughout the addition process, and the temperature of the solution system is kept between 0-5℃. After the addition of solution B is complete, the reaction is carried out at a low temperature of 5℃ for 72 hours, and then centrifuged and freeze-dried to obtain precursor A.
[0085] S4 Precursor A was carbonized and sintered in a nitrogen atmosphere at a temperature of 700℃, a heating rate of 1℃ / min, and a sintering time of 4h. After sintering, it was naturally cooled to room temperature and then dispersed at 1000r / min for 60min to obtain precursor B.
[0086] S5 involves CVD carbon coating of precursor B, heating it to 800℃ at 5℃ / min, and then introducing nitrogen and acetylene at a gas flow rate of 1.5L / min for 3 hours. After naturally cooling to room temperature, the mixture is dispersed and sieved to obtain the co-doped silicon-based material.
[0087] The co-doped silicon-based material prepared in Example 2 was tested and found to have a particle size D50 of 8.3 μm. The silicon particles were coated with a first carbon coating layer containing N and Li elements. The thickness of the first carbon coating layer was about 0.3 μm and the thickness of the second carbon coating layer was about 1.2 μm.
[0088] Example 3
[0089] This embodiment describes a method for preparing a co-doped silicon-based material, which includes the following steps.
[0090] S1 Weigh a certain amount of dimethyl diallyl ammonium chloride and dissolve it in cold water. After the solution is completely dissolved, add a certain proportion of nano-silicon powder and stir evenly to obtain solution A. The molar ratio of dimethyl diallyl ammonium chloride to nano-silicon is 1:30.
[0091] S2 Weigh a certain amount of lithium amino acid and dissolve it in cold water, stir it evenly to obtain solution B; wherein, the molar ratio of lithium amino acid to dimethyl diallyl ammonium chloride in step S1 is 2:1.
[0092] S3. Solution B from step S2 is slowly added dropwise to solution A from step S1. Solution A is stirred throughout the addition process, and the temperature of the solution system is kept between 0-5℃. After the addition of solution B is complete, the reaction is carried out at a low temperature of 5℃ for 72 hours, and then centrifuged and freeze-dried to obtain precursor A.
[0093] S4 Precursor A was carbonized and sintered in a nitrogen atmosphere at a temperature of 700℃, a heating rate of 1℃ / min, and a sintering time of 4h. After sintering, it was naturally cooled to room temperature and then dispersed at 1000r / min for 60min to obtain precursor B.
[0094] S5 involves CVD carbon coating of precursor B, heating it to 800℃ at 5℃ / min, and then introducing nitrogen and acetylene at a gas flow rate of 1.5L / min for 3 hours. After naturally cooling to room temperature, the mixture is dispersed and sieved to obtain the co-doped silicon-based material.
[0095] The co-doped silicon-based material prepared in Example 3 was tested and found to have a particle size D50 of 8.3 μm. The silicon particles were coated with a first carbon coating layer containing N and Li elements. The thickness of the first carbon coating layer was about 0.26 μm and the thickness of the second carbon coating layer was about 1.5 μm.
[0096] Example 4
[0097] This embodiment describes a method for preparing a co-doped silicon-based material, which includes the following steps.
[0098] S1 Weigh a certain amount of dimethyl diallyl ammonium chloride and dissolve it in cold water. After the dissolution is complete, add a certain proportion of silica powder and stir evenly to obtain solution A. The molar ratio of dimethyl diallyl ammonium chloride to silica is 1:10.
[0099] S2 Weigh a certain amount of lithium amino acid and dissolve it in cold water, stir it evenly to obtain solution B; wherein, the molar ratio of lithium amino acid to dimethyl diallyl ammonium chloride in step S1 is 2:1.
[0100] S3. Solution B from step S2 is slowly added dropwise to solution A from step S1. Solution A is stirred throughout the addition process, and the temperature of the solution system is kept between 0-5℃. After solution B is added, the reaction is carried out at a low temperature of 1℃ for 96 hours, and then centrifuged and freeze-dried to obtain precursor A.
[0101] S4 Precursor A was carbonized and sintered in a nitrogen atmosphere at a temperature of 800℃, a heating rate of 1℃ / min, and a sintering time of 5h. After sintering, it was naturally cooled to room temperature and then dispersed at 1000r / min for 60min to obtain precursor B.
[0102] S5 involves CVD carbon coating of precursor B, heating it to 800℃ at 5℃ / min, and then introducing nitrogen and acetylene at a gas flow rate of 1.5L / min for 3 hours. After naturally cooling to room temperature, the mixture is dispersed and sieved to obtain the co-doped silicon-based material.
[0103] The co-doped silicon-based material prepared in Example 4 was tested and found to have a particle size D50 of 6.0 μm. The silicon particles were coated with a first carbon coating layer containing N and Li elements. The thickness of the first carbon coating layer was about 0.35 μm and the thickness of the second carbon coating layer was about 0.8 μm.
[0104] Example 5
[0105] This embodiment describes a method for preparing a co-doped silicon-based material, which includes the following steps.
[0106] S1 Weigh a certain amount of allyltrimethylammonium chloride and dissolve it in cold water. After it is completely dissolved, add a certain amount of silica powder and stir until it is uniform to obtain solution A. The molar ratio of allyltrimethylammonium chloride to silica is 1:5.
[0107] S2 Weigh a certain amount of lithium diethylamino and dissolve it in cold water, stir it evenly to obtain solution B; wherein, the molar ratio of lithium diethylamino and allyltrimethylammonium chloride in step S1 is 1:1.
[0108] S3. Solution B from step S2 is slowly added dropwise to solution A from step S1. Solution A is stirred throughout the addition process, and the temperature of the solution system is kept between 0-5℃. After the addition of solution B is complete, the reaction is carried out at a low temperature of 3℃ for 84 hours. Then, the mixture is centrifuged and freeze-dried to obtain precursor A.
[0109] S4 Precursor A was carbonized and sintered in a nitrogen atmosphere at a temperature of 700℃, a heating rate of 1℃ / min, and a sintering time of 4h. After sintering, it was naturally cooled to room temperature and then dispersed at 1000r / min for 60min to obtain precursor B.
[0110] S5 involves CVD carbon coating of precursor B, heating it to 800℃ at 5℃ / min, and then introducing nitrogen and acetylene at a gas flow rate of 1.5L / min for 3 hours. After naturally cooling to room temperature, the mixture is dispersed and sieved to obtain the co-doped silicon-based material.
[0111] The co-doped silicon-based material prepared in Example 5 was tested and found to have a particle size D50 of 6.0 μm. The silicon particles were coated with a first carbon coating layer containing N and Li elements. The thickness of the first carbon coating layer was about 0.34 μm and the thickness of the second carbon coating layer was about 0.9 μm.
[0112] Comparative Example 1
[0113] This comparative example illustrates a method for preparing a co-doped silicon-based material, comprising the following steps.
[0114] S1 Weigh a certain amount of nano-silicon powder and place it in a rotary furnace. Heat the furnace to 800℃ at 5℃ / min. Introduce nitrogen and acetylene at a gas flow rate of 1.5L / min for 3 hours. After naturally cooling to room temperature, disperse and sieve the powder to obtain carbon-coated nano-silicon precursor A.
[0115] S2 involves secondary carbon coating of nano-silicon precursor A. Nano-silicon precursor A is placed in a rotary furnace and heated to 800℃ at a rate of 5℃ / min. Nitrogen gas is introduced at a rate of 1.5L / min, and acetylene gas is introduced at a rate of 1.5L / min for 3 hours. After natural cooling to room temperature, the material is dispersed and sieved to obtain co-doped silicon-based material.
[0116] Tests conducted on Comparative Example 1 revealed that a first carbon coating layer was coated on the surface of the silicon particles, but this first carbon coating layer did not contain N or Li elements.
[0117] Comparative Example 2
[0118] This comparative example illustrates a method for preparing a co-doped silicon-based material, comprising the following steps.
[0119] S1 Weigh a certain amount of silicon suboxide particles and place them in a rotary furnace. Heat the furnace to 800℃ at 5℃ / min. Then, introduce nitrogen and acetylene at a gas flow rate of 1.5L / min for 3 hours. After naturally cooling to room temperature, the particles are dispersed and sieved to obtain carbon-coated nano-silicon precursor A.
[0120] S2 mixes nano-silicon precursor A with amino lithium evenly to obtain precursor B, with the molar ratio of amino lithium to silicon suboxide in precursor A being 1:5.
[0121] S3 placed precursor B under a nitrogen atmosphere for carbonization and sintering at a temperature of 700℃, a heating rate of 1℃ / min, and a sintering time of 4h. After sintering, it was naturally cooled to room temperature and then dispersed at 1000r / min for 60min to obtain precursor C.
[0122] S4 involves CVD carbon coating of the precursor C, heating it to 800℃ at 5℃ / min, and then introducing nitrogen and acetylene at a gas flow rate of 1.5L / min for 3 hours. After naturally cooling to room temperature, the mixture is dispersed and sieved to obtain the co-doped silicon-based material.
[0123] Tests on the product of Comparative Example 2 showed that the silicon particles were coated with a first carbon coating layer containing N and Li elements.
[0124] Comparative Example 3
[0125] This comparative example illustrates a method for preparing a co-doped silicon-based material, comprising the following steps.
[0126] S1 Weigh a certain amount of nano-silicon powder and mix it evenly with lithium oxalate to obtain a mixture. The molar ratio of lithium oxalate to nano-silicon is 5:1.
[0127] S2 involves heat-treating the mixture from step S1 under a nitrogen atmosphere to achieve pre-lithiation of nano-silicon. The heat treatment temperature is 700℃, the heating rate is 1℃ / min, and the heat treatment time is 5h. After natural cooling, precursor A is obtained.
[0128] S3 involves CVD carbon coating of precursor A, heating it to 800℃ at 5℃ / min, and then introducing nitrogen and acetylene at a gas flow rate of 1.5L / min for 3 hours. After naturally cooling to room temperature, the mixture is dispersed and sieved to obtain the co-doped silicon-based material.
[0129] Comparative Example 4
[0130] This comparative example illustrates a method for preparing a co-doped silicon-based material, comprising the following steps.
[0131] S1 Weigh a certain amount of dimethyl diallyl ammonium chloride and dissolve it in cold water. After the dissolution is complete, add a certain proportion of nano-silicon powder and stir evenly to obtain solution A. The molar ratio of dimethyl diallyl ammonium chloride to nano-silicon is 1:10.
[0132] S2 Weigh a certain amount of lithium amino acid and dissolve it in cold water, stir it evenly to obtain solution B; wherein, the molar ratio of lithium amino acid to dimethyl diallyl ammonium chloride in step S1 is 2:1.
[0133] S3. Solution B from step S2 is slowly added dropwise to solution A from step S1. Solution A is stirred throughout the addition process, and the temperature of the solution system is kept between 0-5℃. After the addition of solution B is complete, the reaction is carried out at a low temperature of 5℃ for 24 hours, and then centrifuged and freeze-dried to obtain precursor A.
[0134] S4 Precursor A was carbonized and sintered in a nitrogen atmosphere at a temperature of 700℃, a heating rate of 1℃ / min, and a sintering time of 4h. After sintering, it was naturally cooled to room temperature and then dispersed at 1000r / min for 60min to obtain precursor B.
[0135] S5 involves CVD carbon coating of precursor B, heating it to 800℃ at 5℃ / min, and then introducing nitrogen and acetylene at a gas flow rate of 1.5L / min for 3 hours. After naturally cooling to room temperature, the mixture is dispersed and sieved to obtain the co-doped silicon-based material.
[0136] Tests on the product of Comparative Example 4 showed that its particle size D50 was 8.3 μm. Further analysis revealed that the silicon particles were coated with a first carbon coating layer containing N and Li elements. The thickness of the first carbon coating layer was approximately 0.2 μm, and the thickness of the second carbon coating layer was approximately 1.1 μm.
[0137] Comparative Example 5
[0138] This comparative example illustrates a method for preparing a co-doped silicon-based material, comprising the following steps.
[0139] S1 Weigh a certain amount of dimethyl diallyl ammonium chloride and dissolve it in cold water. After the dissolution is complete, add a certain proportion of nano-silicon powder and stir evenly to obtain solution A. The molar ratio of dimethyl diallyl ammonium chloride to nano-silicon is 1:70.
[0140] S2 Weigh a certain amount of lithium amino acid and dissolve it in cold water, stir it evenly to obtain solution B; wherein, the molar ratio of lithium amino acid to dimethyl diallyl ammonium chloride in step S1 is 2:1.
[0141] S3. Solution B from step S2 is slowly added dropwise to solution A from step S1. Solution A is stirred throughout the addition process, and the temperature of the solution system is kept between 0-5℃. After the addition of solution B is complete, the reaction is carried out at a low temperature of 5℃ for 72 hours, and then centrifuged and freeze-dried to obtain precursor A.
[0142] S4 Precursor A was carbonized and sintered in a nitrogen atmosphere at a temperature of 700℃, a heating rate of 1℃ / min, and a sintering time of 4h. After sintering, it was naturally cooled to room temperature and then dispersed at 1000r / min for 60min to obtain precursor B.
[0143] S5 involves CVD carbon coating of precursor B, heating it to 800℃ at 5℃ / min, and then introducing nitrogen and acetylene at a gas flow rate of 1.5L / min for 3 hours. After naturally cooling to room temperature, the mixture is dispersed and sieved to obtain the co-doped silicon-based material.
[0144] Tests on the product of Comparative Example 5 showed that its particle size D50 was 8.3 μm. Further analysis revealed that the silicon particles were coated with a first carbon coating layer containing N and Li elements, with a thickness of approximately 0.17 μm and a second carbon coating layer with a thickness of approximately 1.1 μm.
[0145] The co-doped silicon-based materials prepared in Examples 1 to 5 and Comparative Examples 1 to 5 were used as active materials for negative electrode materials, and coin cells were fabricated for electrochemical performance testing. The results are shown in Table 1.
[0146] (1) Charge and discharge performance test
[0147] The co-doped silicon-based materials prepared in Examples 1 to 5 and Comparative Examples 1 to 5 were used as active materials, mixed with polyvinylidene fluoride binder and conductive agent (Super-P) in a mass ratio of 70:15:15, and an appropriate amount of N-methylpyrrolidone (NMP) was added as a solvent to form a slurry. This slurry was coated onto copper foil and then vacuum dried and rolled to prepare a negative electrode. Using lithium metal as the counter electrode, an electrolyte was formed by mixing 1 mol / L LiPF6 with a three-component mixed solvent in an EC:DMC:EMC ratio of 1:1:1 (v / v). A polypropylene microporous membrane was used as the separator, and CR2032 coin cells were assembled in a glove box filled with protective gas. Charge-discharge tests of the coin cells were conducted on the LANHE battery testing system of Wuhan Landian Electronics Co., Ltd. Under normal temperature conditions, the voltage is charged and discharged at a constant current of 0.1C to 0.01V, then discharged at a constant current of 0.02C to 0.005V, and finally charged at a constant current of 0.1C to 1.5V. The capacity at 1.5V is the initial charge capacity, and the ratio of the initial charge capacity to the initial discharge capacity is the initial coulombic efficiency.
[0148] (2) Cyclic performance test
[0149] The co-doped silicon-based materials prepared in Examples 1 to 5 and Comparative Examples 1 to 5 were mixed with graphite at a mass ratio of 0.15:0.85 and used as active materials. These materials were then mixed with an aqueous dispersion of acrylonitrile copolymer (LA132, 15% solid content) as a binder and a conductive agent (Super P) at a mass ratio of 70:10:20. A suitable amount of water was added as a solvent to form a slurry, which was then coated onto copper foil and vacuum dried and rolled to prepare a negative electrode. Using lithium metal as the counter electrode, and a 1 mol / L LiPF6 three-component mixed solvent at a volume ratio of EC:DMC:EMC = 1:1:1, a polypropylene microporous membrane was used as the separator. The cells were assembled into CR2032 coin cells in an inert gas-filled glove box. Charge-discharge tests of the coin cells were conducted on a battery testing system from Landian Electronics Co., Ltd., under normal temperature conditions, with a constant current charge-discharge of 0.1C and a charge-discharge voltage limited to 0.005–1.5V. Calculate the capacity retention rate after 100 cycles.
[0150] Table 1 Test Results
[0151]
[0152] As shown in Table 1, Examples 1 to 5, prepared using the co-doped silicon-based material preparation method of the present invention, exhibit excellent initial charge capacity and initial coulombic efficiency when used as anode materials in lithium-ion batteries, with good capacity retention. This is mainly due to the formation of a first carbon coating layer on the surface of silicon particles in the co-doped silicon-based material of the present invention. The carbon layer in the first carbon coating layer is tightly bonded to the silicon particles by chemical bonds, and N and Li elements are uniformly distributed on the first carbon coating layer. N doping can improve the conductivity of the silicon-based material. As a silicon-based anode material, pre-lithiation can significantly improve the initial coulombic efficiency of the silicon-based anode material, thereby increasing the battery capacity and energy density. Moreover, the chemical bonding between the first carbon coating layer and the silicon particles improves the cycle stability of the anode material compared to conventional physical coating. Therefore, the co-doped silicon-based material of the present invention, used as an anode active material in lithium-ion batteries, is beneficial for the widespread application of high-energy-density lithium-ion batteries.
[0153] In Comparative Example 1, without the introduction of N and Li elements, the material needs to form an SEI film during charging and discharging, which consumes the Li element in the electrolyte, resulting in low capacity and efficiency of the material, as well as poor cycle performance.
[0154] Both Comparative Examples 2 and 3 used physically blended lithium salts. The lithium salt used in Comparative Example 2 contained nitrogen, while the lithium salt used in Comparative Example 3 did not contain nitrogen. The physical blending method used in Comparative Examples 2 and 3 resulted in uneven mixing between the lithium salt and the material, leading to poorer cycle performance of the material compared to the material prepared in this invention.
[0155] In Comparative Example 4, the reaction time during the preparation of the first carbon coating layer was only 24 hours. Therefore, the thickness of the first carbon coating layer was thin and the content of Li element was low. Consequently, the efficiency and cycle performance of the material prepared in Comparative Example 4 were poor.
[0156] In Comparative Example 5, the molar ratio of double-bonded ammonium chloride salt compound to nano-silicon in the preparation process of the first carbon coating layer is 1:70. This also results in a thinner first carbon coating layer and a lower Li content. Compared with the material prepared by the preparation method of the present invention, the material prepared in Comparative Example 5 has lower efficiency and cycle performance.
[0157] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.
Claims
1. A method for preparing a co-doped silicon-based material, characterized in that, Including the following steps: S1 Dissolves a double-bonded ammonium chloride salt compound in water, adds silicon particles and stirs until homogeneous to obtain solution A, wherein the molar ratio of the double-bonded ammonium chloride salt to the silicon particles is 1:4 to 1:40; S2 dissolves the lithium-nitrogen compound in water to obtain solution B; S3. Solution B is added dropwise to solution A while stirring. After the addition is complete, the mixture is reacted at a certain temperature. After the reaction is completed, the mixture is centrifuged and freeze-dried to obtain powder precursor A. The reaction temperature is controlled at 0 to 5°C and the reaction time is controlled at 48 to 96 h. S4 carbonizes and sinters the powder precursor A to obtain precursor B; S5. Carbon coating is performed on the precursor B to obtain a co-doped silicon-based material. The co-doped silicon-based material includes silicon particles and a first carbon coating layer covering the surface of the silicon particles, forming silicon particles containing the first carbon coating layer. A plurality of the silicon particles containing the first carbon coating layer are embedded in a second carbon coating layer. The first carbon coating layer is chemically bonded to the silicon particles, and the first carbon coating layer contains nitrogen and lithium elements.
2. The method for preparing co-doped silicon-based materials according to claim 1, characterized in that, The mass percentage of nitrogen in the co-doped silicon-based material is 8-15%.
3. The method for preparing co-doped silicon-based materials according to claim 1 or 2, characterized in that, The mass percentage of lithium in the co-doped silicon-based material is 6-12%.
4. The method for preparing co-doped silicon-based materials according to claim 1, characterized in that, The co-doped silicon-based material comprises any one of the following characteristics ① to ⑩: ①The silicon particles are at least one of nano-silicon or silicon suboxide; ②The silicon particles are nano-silicon, and the particle size D50 of the nano-silicon is 1 to 150 nm; ③ The silicon particles are nano-silicon, and the grain size of the nano-silicon is 1 to 15 nm; ④ The silicon particles are silicon suboxide, and the silicon suboxide is SiO x x satisfies 0 < x ≤ 0.8; ⑤ The molar ratio of Li content to silicon particle content in the first carbon coating layer is 0.05 to 0.25:1; ⑥ The molar ratio of N content to silicon particle content in the first carbon coating layer is 0.05 to 0.25:1; ⑦ The thickness of the first carbon coating layer is 0.3 to 1.0 μm; ⑧ The second carbon coating layer is a single carbon coating layer or at least two carbon coating layers; ⑨ The second carbon coating layer is a single-layer carbon coating layer with a thickness of 0.5 to 2 μm; ⑩ The particle size D50 of the co-doped silicon-based material is 3 to 50 μm.
5. The method for preparing co-doped silicon-based materials according to claim 1, characterized in that, Includes at least one of the following features (1) to (4): (1) The double-bonded ammonium chloride salt compound is selected from at least one of dimethyl diallyl ammonium chloride, diethyl diallyl ammonium chloride, triallyl methyl ammonium chloride, and allyl trimethyl ammonium chloride; (2) The lithium nitrogen compound is selected from at least one of lithium amino, lithium dimethylamine, lithium diethylamino, and lithium diisopropylamino; (3) The molar ratio of the amino content of the lithium nitrogen compound to the double bond content of the double-bonded ammonium chloride salt is 1 to 5:1; (4) The carbonization temperature is 500 to 1200℃.
6. The application of the co-doped silicon-based material prepared by the method of any one of claims 1 to 5 in the negative electrode active material.
7. The application according to claim 6, wherein the negative electrode active material is used in a lithium-ion battery.
Citation Information
Patent Citations
Preparation method of silicon-carbon negative electrode material for lithium ion battery
CN112551522A
Preparation method of nitrogen-doped pre-lithiated silicon monoxide material as well as product and application of nitrogen-doped pre-lithiated silicon monoxide material
CN116799187A
Silicon-based negative electrode material, preparation method thereof and lithium ion battery
CN115332488A
Nitrogen-lithium co-doped silicon-carbon composite material as well as preparation method and application thereof
CN116314649A